AT THE STAGE OF IN-DEPTH SPECIALIZATION PROBLEMS OF MANAGING THE TRAINING PROCESS OF LONG-DISTANCE RUNNERS - Sultanov Usman Ibragimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
A systematic approach to the management of sports training determines the need to take into account the characteristics of the model model of the athlete. These descriptions show the main components of the activity in Real (real) units of measurement. According to experts, it was cited that the need to study the future showing results, States of controlled objects is one of the main tasks of managing the process of sports training.